Evaluation of Circularity in Chilean Companies: An Approach from the Circular Value Chain Model - Carlos GALLEGUILLOS; Daniela TOLMO; Rubén HURTADO; Rafael FIGUEROA; José SILVA (Communications of International Proceedings, 2023)
The objective of this research is to evaluate circularity in Chile, through the circular value chain (CVC) model. This is relevant because the results can lead to more efficient practices within companies, thus contributing to the development of sustainability at a global level. Surprisingly, there are few instruments for evaluating circularity applied to developing economies in Latin America. Thus, this research aims to fill this gap in the literature. To this end, a methodology was established that included a descriptive approach, where the non-probabilistic sample reached 111 Chilean companies. The main finding indicates that large companies lead and present the highest scores per variable and in total value according to the CVC criteria, followed by medium-sized companies, and lastly are micro and small companies. This is probably due to their resources and capabilities. Finally, the conclusions and recommendations are presented.
Keywords: Circularity; circular economy; circular value chain